Representasi Tindak Tutur Calon Gubernur Sulawesi Selatan: Analisis Wacana Kesopanan Berbahasa - Yusri, Yusri; Handayani, Yuni; Riskawati, Riskawati (UI Scholars Hub, 2012)
The research looks into the Governor Candidate of South Sulawesi’s representation of speech acts leading up to the governor’s election in 2013, in particular into politeness and the relation between cultural speech acts in South Sulawesi society and universal politeness maxim. The research is qualitative with pragmatic approach. This research uses written data from the utterances of the South Sulawesi’s incumbent Governors printed in the biggest mass media in South Sulawesi—Harian Fajar and Tribun Timur—for 4 months, in April, May, June, and July. The data, in the form of utterances produced by the politicians, are analyzed based on maxims that are universally used to show politeness towards their addresses. In analyzing meanings, researchers also consider the cultural context in which speech acts occured in South Sulawesi society. The maxim involved tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. The research finds that the utterances by the incumbent Governors of South Sulawesi conform to politeness maxim in accordance with approbation maxim, while the utterances by the governor candidate of South Sulawesi that violate the politeness maxim tend to adhere to modesty maxim. Utterances that are analyzed show that the utterances produced by the governor candidate of South Sulawesi are more likely to conform to politeness maxim. Several utterances that are interpreted within South Sulawesi cultural context of speech acts show that there is appropriateness between cultural speech act in South Sulawesi society and maxim of politeness used in this research.